2014
DOI: 10.1080/0028825x.2013.862554
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria in New Zealand indigenous grasslands

Abstract: We review current knowledge of cyanobacterial diversity and abundance in New Zealand's indigenous tussock grassland soils and present preliminary results on microbial diversity in grassland soils. A cyanobacterial community of eight operational taxonomic units was present in soil samples from Deep Stream indigenous grassland. This included strains belonging to the orders Chroococcales, Oscillatoriales and Nostocales. UniFrac analysis showed that the cyanobacterial populations were significantly different betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 128 publications
(143 reference statements)
1
3
0
Order By: Relevance
“…Members belonging to Planctomycetes have been reported as major groups to decompose heteropolysaccharide [39] and chitin [40] and are involved in the C cycle in soils, which might be related to the highest Ctot content being in OP soil. OTUs from Cyanobacteria are photoautotrophs and play key roles in biogeochemical processes in nature and improve the turnover of C and N in the soil [41]. In addition, we also observed that the archaeal phylum Crenarchaeota was significantly increased in CP.…”
Section: Differential Taxa For Cultivation Systemssupporting
confidence: 51%
See 1 more Smart Citation
“…Members belonging to Planctomycetes have been reported as major groups to decompose heteropolysaccharide [39] and chitin [40] and are involved in the C cycle in soils, which might be related to the highest Ctot content being in OP soil. OTUs from Cyanobacteria are photoautotrophs and play key roles in biogeochemical processes in nature and improve the turnover of C and N in the soil [41]. In addition, we also observed that the archaeal phylum Crenarchaeota was significantly increased in CP.…”
Section: Differential Taxa For Cultivation Systemssupporting
confidence: 51%
“…and Pseudoxanthomonas spp. have been shown as N fixers [41,42]. OTUs within the genera Glycomyces and Leptolyngbya could inhibit other pathogens by producing antibiotics (e.g., streptomycin) [43,44].…”
Section: Differential Taxa For Cultivation Systemsmentioning
confidence: 99%
“…Two new families, Tolypothrichaceae and Godleyaceae, were established to reflect phylogenetic findings after a molecular assessment of the Microchaetaceae (Hauer et al, 2014). New Zealand indigenous grasslands explored with both traditional and molecular techniques, contained eight taxonomical units of cyanobacteria that differed between burned and unburned soil (Chua et al, 2014). Rather than temperature or time, an increase in periphyton biomass, correlated with an increase in total macroinvertebrate biomass and abundance of scrapers in stream reaches located along a disturbance gradient of canopy cover and with agriculturally derived nutrients (Braccia et al, 2014).…”
Section: Aerophilic Subaerophilic and Subterraneanmentioning
confidence: 99%
“…grandicosta. The work by Chua et al (2014), from the Department of Botany at Otago University, reviews the current knowledge of cyanobacterial diversity in New Zealand's indigenous tussock grasslands and outlines the different techniques available to investigate cyanobacterial diversity in terrestrial ecosystems -the authors provide a comparison of the advantages and limitations of both traditional approaches, such as isolating strains on selective media, with more recent developments utilising high-throughput sequencing technologies.…”
Section: Algal and Cyanobacterial Bioenergy And Diversitymentioning
confidence: 99%